Les difficultés à nommer le nouveau régime de croissance - Mickaël Clévenot (Revue de la Régulation)
The main proponents of the French regulation theory agree with the idea that finance has become the most important element in the going recomposition of capitalism. The current situation is marked by financial instability. Under these conditions, it seems difficult to assess the emergence of a new mode of accumulation. Indeed, identifying a mode of accumulation requires both the recognition of institutional coherences and of systemic stability. Whereas the existence of new coherences carried by new actors is relatively clear, global stability can hardly characterizes today's economic situation. These hiatus explains the difficulty to qualify the new patterns. These issues will be scrutinized in detail in this paper.